Intellectual assets and knowledge audit as a fundamental step for the "University of the Future" transformation - Ahmad Dahlan, Abdul Rahman; Abdullah, Sarifah; Wahiddin, Mohamed Ridza (IEEE, 2016)
The higher education sector is undergoing a fundamental transformation, as the forces of globalization and technology have transformed other industries of the economy in the past 20 years. The industry is driven by a number of drivers of change where some of them are disruptive. Universities will have to transform the way they deliver their services, administer their organizations, and manage their intellectual assets and knowledge in creating values and virtues. The purpose of this paper is to present the methodology deployed and the findings of a knowledge audit (KA) at a Malaysian Institution of Higher Learning (IHL). This paper gives a high level description of the conducted KA methodology, as one of the early strategic initiatives on embarking the transformation journey to "University of the Future" or in short UotF. The KA attempted to address the most critical intellectual assets & knowledge requirements of a typical IHL. The audit helped to make the intellectual assets & knowledge in the IHL visible, helped the IHL to understand its value and contribution to the IHL excellence and transformation journey to UotF.